Toll-like receptor 2 (TLR2) is a marker of angiogenesis in the necrotic area of human medulloblastoma - Maslinska, Danuta; Laure-Kamionowska, Milena; Maslinski, Sławomir; Szukiewicz, Dariusz (Folia Neuropathologica, 2015)
Angiogenesis plays a key role in the progression of malignant tumors. In recent years, anti-angiogenic drugs have been shown to be effective against tumors. However, some tumors are able to adopt escape mechanisms, suggesting that the vascular network in these tumors may be formed or may function in a different way. Medulloblastomas are tumors characterized by poor prognosis and low patient survival rates. These tumors rarely metastasize, but the reason why they almost always recur locally is not known. Central to mediating neoplastic changes is the interaction between cell surface receptors and their cognate ligands, which through intracellular signaling induce alternations in gene expression. In this context, the aim of our present study was to examine in medulloblastoma the distribution of Toll-like receptor 2 (TLR2) and receptor for advanced glycosylation end-product (RAGE), and mast cells associated with the tumor neovascularization process. Immunohistochemical study with a battery of specific antibodies was used. The results show that in the tumor necrotic area, TLR2 participates in all steps of vascular network formation, but in regions where the tumor was not affected by necrosis, the capillary network was TLR2 immunonegative. The TLR2 vascular network of the necrotic area was not associated with RAGE and mast cells. However, in the region of the medulloblastoma not affected by necrosis, the RAGE receptor was present in the endothelium of all capillaries, and mast cells were numerous only in the perivascular space of large brain and meningeal vessels at the border of the tumor. In conclusion, our results show that the receptor of innate immunity TLR2 plays an important role in recognition of ligands delivered by dying necrotic medulloblastoma cells and participates in tumor neovascularization. Moreover, the results show that the RAGE receptor and mast cells operate in different medulloblastoma regions and influence different parts of the tumor vascular network.